(N2H6)[HPO3F]2: maximizing the optical anisotropy of deep-ultraviolet fluorophosphates. Issue 37 (19th April 2022) - Qiu, Haotian; Li, Fuming; Jin, Congcong; Lu, Juanjuan; Yang, Zhihua; Pan, Shilie; Mutailipu, Miriding
Abstract : A new metal-free monofluorophosphate with a large birefringence has been reported. The reported birefringence sets a record among fluorophosphates and it originates from the preferential arrangement of non-π-conjugated [HPO3 F] units. Abstract : Although phosphates are a rich source of deep-ultraviolet optical materials, the realization of large optical anisotropy in them still remains a challenge because of the small polarizability anisotropy of [PO4 ] units. Inspired by the fluoridation strategy and hydrogen bond interaction, a new metal-free monofluorophosphate, (N2 H6 )[HPO3 F]2, was synthesized, which exhibits a large birefringence (cal. 0.077) and wide band gap (∼6.51 eV). Such a large birefringence in (N2 H6 )[HPO3 F]2 sets a new record among available fluorophosphates, and the [HPO3 F] unit is theoretically confirmed to be a new birefringence-active unit.